Peringatan Dini Pencemaran Logam Berat dan Pestisida Berdasarkan Rasio Seks Anakan Daphnia sp. - Ahmad S. Mubarak; Juni Triastuti (Universitas Gadjah Mada, 2009)
Pesticides and heavy metal are the major contributor for environmental pollution and have been spread out widely in aquatic environments. Daphnia sp. is a zooplankton that mostly used to detect aquatic pollution. The aim of this research was to study the effect of exposuring different concentration of heavy metal (Pb and Cd) and pesticides (diazionin) to the sex ratio offspring of Daphnia sp. The experiment composed of three kind of treatments (Cd, Pb and diazinon), each consist of 5 treatments namely 25%, 50%, 75%, 100% and 0% as control, and 4 replications. The data was analyzed with Kruskal Walace. If there was any different in each treatment, then was analyzed with Duncan Double Gap Test and linear regression. The research showed that exposuring Cd, Pb and diazinon with different concentration to the Daphnia sp. during 96 hours could increase the percentage male offspring of Daphnia sp. Concentration of Pb, Cd and peticides gave positive correlation to the sex ratio offspring of Daphnia sp. Further research was needed to know the practical technology using sex ratio offspring of Daphnia sp. to detect the level of pollution.